PEMANFAATAN DAGING BUAH KUINI DALAM PEMBUATAN PRODUK FRUIT LEATHER DENGAN PENAMBAHAN DAGING BUAH NAGA MERAH - Putri, Kurnia; Herawati, Netti; Hamzah, Faizah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Fruit leather type of food made from fruit that have been crushed and dried. Fruit leather has a storage period of up to 12 mounth if kept in good storage conditions. One of the criterationfordeterminan the quality of fruit leather is color. The fruit used is not just the fruit of this kuini but combined with red dragon fruit to color interesting and also dragon fruit contain useful pigment. This study aims to determine the best characteristic of the concentration of fruit kuini and red dragon fruit in the manufacture of quality fruit leather product. Treatment used KN1 (50% kuini fruit, 50% red dragon fruit), KN2 (60% kuini fruit, 40% red dragon fruit), KN3 (70% kuini fruit, 30% red dragon fruit), KN4 (80% kuini fruit, 20% red dragon fruit), KN5 (90% kuini fruit, 10% red dragon fruit). The data obtained were analyzed statistically by using Anova and DNMRT at 5%. The result showed that the use of kuini and red dragon fruit significantly affect the water content, ash content, acidity degree, coarse fiber content, sucrose content, and organic assessment. The best fruit leather the results of this study is fruit leather with KN3 treatment, which has a 12,08% of water content, 0,89% ash content, 4,40% acidity degree, 1,12% crude fiber content, 58,57% sucrose content. Descriptive assessment shows the result that is the color is yellowish red, the aroma tends to smell the fruit of kuini and red dragon fruit, sweet taste, chewy texture and the hedonic overall assessment fruit leather favored by panelists. Keywords: fruit leather, kuini fruit, and red dragon fruit